Rigid DNA Beams for High‐Resolution Single‐Molecule Mechanics1. Issue 30 (21st June 2013) - Pfitzner, Emanuel; Wachauf, Christian; Kilchherr, Fabian; Pelz, Benjamin; Shih, William M.; Rief, Matthias; Dietz, Hendrik
<x xml:space="preserve">Abstract</x> Bridging the gap: Rigid DNA linkers (blue, see picture) between microspheres (green) for high‐resolution single‐molecule mechanical experiments were constructed using DNA origami. The resulting DNA helical bundles greatly reduce the noise generated in studies of conformation changes using optical tweezers and were applied to study small DNA secondary structures.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>